Entre a estrutura institucional e a conjuntura política: o Programa Nacional de Produção e Uso do Biodiesel (PNPB) e a combinação inclusão social-participação - Pedroti, Paula Maciel (2011)
This thesis analyses the decision‐making process of Programa Nacional de Produção e Uso do Biodiesel (PNPB), highlighting its two main characteristics: (1) PNPB’s goals, that aim to promote sociaThis  thesis analyses  the  decision‐making  process  of  Programa Nacional de Produção e Uso do Biodiesel (PNPB), highlighting its two main characteristics: (1) PNPB’s goals, that aim to promote social inclusion – a new content in the agro‐energy policy environment – and  (2)  its  innovating  decision  process,  which  brought  to  negotiation  actors  whose interests  are  historically  divergent  –  biodiesel  producers,  agribusiness  and  family farming  representatives.  The  research,  based  on  institutional  analysis  of  Brazilian political system in association with theoretical approaches of public policies focused on the  role  of  the  actors,  built  the  hypothesis  that  the  specificities  of  PNPB’s  decision - making  process  are  explained  not  only  by  the influences  of  the  institutional  structure introduced with the Federal Constitution of 1988 but also by the political context. PNPB was  formulated during  the presidency of Lula, whose government  strategy was guided by  the  combination  social  inclusion/  participation.  The  thesis  used  the  controlled comparison  method  and  analyzed  two  agro‐energy  policies,  namely  Proálcool  and Probiodiesel,  both  formulated  before  PNPB,  in  different  institutional  and  political environments.